"According to the Polls…" Opinion Poll Coverage in Network Evening News during the 2020 U.S. Election Campaign. (4th September 2021) - Beckers, Kathleen
Abstract: After news media and pollsters were unsuccessful in predicting recent political outcomes such as the 2016 U.S. election, opinion polls came under scrutiny. Journalists were accused of not providing audiences the tools to correctly interpret poll information. Using a content analysis of all evening news items from CBS, ABC, and NBC from the final two months before the 2020 U.S. general election, we analyzed the quality of poll coverage. We find that half of the references to election polls are "diffuse, " in which journalists refer to "the polls" in a general manner. When news items do cover specific poll results, media often disclose the absolute minimal essential information (e.g., population and error margin), but fail to provide additional methodological details.